Karakteristik Leukemia Limfoblastik Akut pada Anak di Rumah Sakit Kanker Dharmais 2000-2008 - ANKY TRI RINI; MURURUL AISY; YUNI ASRI; EDI - (Indonesian Journal of Cancer, 2010)
Acute lymphoblastic leukemia (ALL) is the most common cancer found in children below 14 years old. It characterized by abnormal white blood cell proliferation which replace normal bone marrow component with pallor, headache, organomegaly, fever, bone pain and bleeding as its clinical manifestation. Acute lymphoblastic Leukemia (ALL) is very important problem in childhood cancer. As one strategy to improve cancer management, specially ALL, epidemiology description and patient outcome is needed. Based on our study in Dharmais Cancer Hospital (2000-2008), ALL is frequent in boy and particularly lie between 1-5 years old. ALL L1 is the most common type of ALL, and majority cases are standard risk. We observed 44,9% mortality,survive 27,5 %. Unfortunately there were many patients loss to follow up (27,5%) and event free survival rates for ALL in Dharmais Cancer Hospital is 38,1%.